ANALISIS PENERAPAN MANAJEMEN KESISWAAN DI MADRASAH ALIYAH MIFTAHUL ULUM MUKOMUKO - Maula Desiono (STIT AL MULTAZAM, 2019)
Student management in Madrasah Aliya Miftahul Ulum has followed the concepts of student management, this can be seen directly in the implementation of new student admissions, data collection on student learning progress, guidance and guidance on student discipline and monitoring has been implemented by the madrasa component. There are obstacles to the implementation of student management. Based on the results of this study into the material of thought, information and input for organizers and coaches of students, administrators, principals, teachers, and other staff in the Madrasah Aliyah Miftahul Ulum, users of education services (community, guardians of students, students) and education observers in managing students better in order to produce quality resources and generations, can produce graduates who are strong and ready to face the challenges of the future.